2015
DOI: 10.1016/j.childyouth.2015.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Needs-led child and youth care: Main characteristics and evidence on outcomes

Abstract: a b s t r a c tNeeds-led child and youth care has three main characteristics: a continuous focus on clients' needs, client participation in the care process (including decision making), and practitioners' displays of needs-led attitudes and skills. The primary aim of this review was to establish whether there is evidence for using a needs-led approach when working with children and families in need. We performed a literature search to find reviews and outcome studies of child and youth care for school-aged chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 45 publications
0
6
1
Order By: Relevance
“…Evidence is also lacking as to whether care outcomes vary depending on the alignment of type of problems with type of psychosocial care. Such knowledge is needed to optimize the access of children and adolescents to psychosocial care, to deliver care that is need-oriented, and to improve care outcomes [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence is also lacking as to whether care outcomes vary depending on the alignment of type of problems with type of psychosocial care. Such knowledge is needed to optimize the access of children and adolescents to psychosocial care, to deliver care that is need-oriented, and to improve care outcomes [ 4 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a previous study indicated that children and adolescents want to feel that they are taken seriously (van Bijleveld et al 2015). This finding is contrary to needs-led child care (Metselaar et al 2015) and "child-friendly care" guidelines (Lenton et al 2014). The main characteristics of this approach are: focusing on clients' needs, enabling them to participate in the care process, including decisionmaking, and employees displaying needs-led attitudes and skills (listening to clients and working in active partnership with them) in daily practice (Lenton et al 2014;Metselaar et al 2015).…”
Section: Accessibility and Acceptability Of Servicesmentioning
confidence: 86%
“…Moreover, the involvement of parents as a contribution to treatment for children diagnosed with ASD is recommended (Boer & Van der Gaag, 2016;Hungate, Gardner, Tackett, & Spencer, 2018;Van Rooyen & Rietveld, 2017). Research shows that an active participating role of clients in mental health care services generally contributes to achieving positive outcomes (Metselaar, Knorth, Van Yperen, Van den Bergh, & Horstman, 2016;Metselaar, Van Yperen, Van den Bergh, & Knorth, 2015).…”
Section: Reflection On the Role Of Participantsmentioning
confidence: 99%
“…Clients are an important source of information about, for instance, the connection of a treatment with the children's needs. For research aims children's feedback may contribute to improvement of the intervention (Metselaar et al, 2015(Metselaar et al, , 2016.…”
mentioning
confidence: 99%